2018
DOI: 10.1186/s12969-018-0237-x
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of microcirculation and vascular responsiveness in adolescents with primary Raynaud phenomenon

Abstract: Background Raynaud’s phenomenon (RP) is a functional vascular disease, presenting with recurrent episodes of ischemia of extremities in response to cold and emotional stress. Investigating cutaneous microcirculation is an important tool in understanding the complex neuro-immuno-vascular interactions in its pathophysiological mechanisms. Since there is no available data on vascular responsiveness in RP in the paediatric population, we investigated skin perfusion and heat-induced hyperaemia in comparison with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…But, the peripheral microcirculatory adaptations to cold exposure-response is known to be unpredictable (67). The cold provocation test is commonly used to study Raynaud's phenomenon, systematic sclerosis, and other conditions (68)(69)(70)(71). However, few studies have been conducted to explore the neurovascular responses in people with diabetes (61,72,73).…”
Section: Cold Perception Mediated By Small Fiber Nervesmentioning
confidence: 99%
“…But, the peripheral microcirculatory adaptations to cold exposure-response is known to be unpredictable (67). The cold provocation test is commonly used to study Raynaud's phenomenon, systematic sclerosis, and other conditions (68)(69)(70)(71). However, few studies have been conducted to explore the neurovascular responses in people with diabetes (61,72,73).…”
Section: Cold Perception Mediated By Small Fiber Nervesmentioning
confidence: 99%
“…Diagnosis is largely clinical, but other methods are being explored including laser flow Doppler. Doppler allows detection of microcirculation changes, which may aid in early detection and establishing a more accurate prognosis [50]. Treatment includes trigger avoidance and medical management (i.e., calcium channel blockers, nitric oxide, etc.)…”
Section: Raynaud's Phenomenonmentioning
confidence: 99%
“…The impaired endothelial dysfunction demonstrated in both primary and secondary RP in previous studies. Furthermore it was shown that microvascular derangement was found as associated with endothelial dysfunction in RP patients 11,12 . The endothelium has an important role in the regulation of vascular response against blood flow-associated shear stress and ischemia-reperfusion events.…”
Section: Discussionmentioning
confidence: 99%